Stages of development of distance education in Ukraine (Pedagogy of Higher and Secondary Education, 2012)
Shynkarenko L. I. Stages of development of distance education in Ukraine.The article considers formation and development stages of the Ukrainian system of education by correspondence, which continually extends perception of the world complexity and informative society formation.
Keywords: education by correspondence; professional training; information technologies; advanced training